Sex differences in incidence of out-of-hospital cardiac arrest across ethnic and socioeconomic groups: A population-based cohort study in the Netherlands. (15th November 2021) - Bolijn, Renee; Sieben, Cenne H.A.M.; Kunst, Anton E.; Blom, Marieke; Tan, Hanno L.; van Valkengoed, Irene G.M.
Abstract: Background: Insight into the occurrence of out-of-hospital cardiac arrest (OHCA) within general populations may help to target prevention strategies. Case registries suggest that there may be substantial differences in emergency medical service (EMS)-attended OHCA incidence between men and women, but relative sex differences across ethnic groups and socioeconomic (SES) groups have not been studied. We investigated sex differences in OHCA incidence, overall and across these subgroups. Methods: We performed a retrospective population-based cohort study, combining individual-level data on ethnicity and income (as SES measure) from Statistics Netherlands of all men and women aged ≥25 years living in one study region in the Netherlands on 01-01-2009 ( n  = 1, 688, 285) with prospectively collected EMS-attended OHCA cases ( n  = 5676) from the ARREST registry until 31-12-2015. We calculated age-standardised incidence rates of OHCA. Sex differences were assessed with Cox proportional hazards regression analyses, adjusted for age, ethnicity and income, in the overall population, and across ethnic and SES groups. Results: The age-standardised incidence rate of OHCA was lower in women than in men (30.9 versus 87.3 per 100, 000 person-years), corresponding with a hazard ratio (HR) of 0.33 (95% confidence interval [CI] 0.31–0.35). These sex differences in hazard for OHCA existed in all income quintiles (HR range: 0.30–0.35) and ethnic groups (HR range: 0.19–0.40), except among Moroccans (HR 0.89, 95% CI 0.51–1.57). Conclusion: Women have a substantial, yet lower OHCA incidence rate than men. The magnitude of these sex differences did not vary across social strata. Highlights: EMS-attended OHCA incidence rates were calculated in 1.7 million men and women. OHCA incidence was substantial: 87.3 (men), 30.9 (women) per 100, 000 person-years. Sex differences were consistent across SES groups and most ethnic groups. Men are an important target group for OHCA prevention strategies. Due to differential aetiology and lower survival rates, women will also benefit.